Die bilanzrechtliche Abbildung von Blockchain-basierten Zahlungsmitteln Eine Untersuchung nach Handelsrecht und IFRS - Braun, Marcus (Mohr Siebeck, 2023)
How should companies deal with cryptocurrencies in their financial statements? The current lack of a specific accounting standard here leads Marcus Braun to investigate how blockchain-based cryptocurrencies could be treated under existing International Financial Reporting Standards (IFRS) and commercial law in Germany.
PublicationDate: 20230719
Keywords: Minderheitsaktionäre -- Jahresabschluss -- distributed ledgers -- Bitcoin -- Kryptowährungen -- Quing-Dynastie -- Bilanzierung -- Mining -- Südtirol -- Handels- und Gesellschaftsrecht, Wirtschaftsrecht, Steuerrecht -- Wirtschaftsrecht -- Betriebswirtschaftslehre